Education, entertainment, and indoctrination : educational film in interwar China - Li, Kaiyi (Journal of educational media, memory, and society, 2020)
This article demonstrates how educational film in interwar China served the dual purpose of mass recreation and political indoctrination. It places educational film in China in the context of Chinese tradition and the predominance of utilitarian scholarship. On the one hand, China has a long history of using mass-recreational tools in order to influence and control society. On the other hand, foreign educational films available in the early twentieth century were not attractive to Chinese audiences. Hence, the boundary between recreational and educational film at the time was ambivalent and the combination of recreation, education, and propaganda was reflected both in the phenomenon of showing educational films and in the contents of the films themselves.